Европейское соглашение о международной перевозке опасных грузов по внутренним водным путям (ВОПОГ) 2023 - United Nations Economic Commission for Europe (United Nations, 2023)
The European Agreement concerning the International Carriage of Dangerous Goods by Inland Waterways (ADN) done at Geneva on 26 May 2000 under the auspices of the United Nations Economic Commission for Europe (UNECE) and the Central Commission for Navigation on the Rhine (CCNR) has been in force since February 2008. The Regulations annexed to the ADN contain provisions concerning dangerous substances and articles, their carriage in packages and in bulk on board inland navigation vessels or tank vessels, as well as provisions concerning the construction and operation of such vessels. They also address requirements and procedures for inspections, the issue of certificates of approval, recognition of classification societies, monitoring, and training and examination of experts. They are harmonized to the greatest possible extent with the dangerous goods agreements for other modes of transport.